Ketentuan Hukum Terhadap Pengelolaan Limbah Pada Pembangunan Ibu Kota Negara Baru (IKN) di Kalimantan Timur - Alamuddin, Imam; Wijaya, Andy Usmina (Universitas Gorontalo, 2025)
Until now, development activities are still ongoing in the New State Capital of IKN in East Kalimantan, the government has the responsibility to treat waste generated from IKN development processors. Construction waste consists of various types of materials produced by the development of the IKN such as wood, metal, concrete, plastic, air, pieces of iron, noise and also dangerous liquids with a large scale of development projects. Provisions regarding waste itself are regulated in several Laws and Regional Regulations, for example, regulated in Law Number 32 of 2009 concerning Environmental Protection and Management, and Regional Regulation No. 2 of 2016 concerning Waste Management. The purpose of this study is to find out and analyze the impact of waste in the IKN by incorporating it into the applicable Regional Laws and Regulations in Indonesia. The research method used is normative juridical research with a legislative approach and a conceptual approach. The technique of collecting legal data using primary and secondary materials used in this study is a literature study. The results of the analysis are waste management by reducing, moving, recycling and final disposal of waste, making wastewater treatment plants using environmentally friendly sanitation technology, and making disposal sites and processing waste produced by placing several points in IKN. The implementation of waste management in the development of the IKN is important to ensure that the development does not harm the environment and society. By implementing proper waste management in the development of IKN.Until now, development activities are still ongoing in the New State Capital of IKN in East Kalimantan, the government has the responsibility to treat waste generated from IKN development processors. Construction waste consists of various types of materials produced by the development of the IKN such as wood, metal, concrete, plastic, air, pieces of iron, noise and also dangerous liquids with a large scale of development projects. Provisions regarding waste itself are regulated in several Laws and Regional Regulations, for example, regulated in Law Number 32 of 2009 concerning Environmental Protection and Management, and Regional Regulation No. 2 of 2016 concerning Waste Management. The purpose of this study is to find out and analyze the impact of waste in the IKN by incorporating it into the applicable Regional Laws and Regulations in Indonesia. The research method used is normative juridical research with a legislative approach and a conceptual approach. The technique of collecting legal data using primary and secondary materials used in this study is a literature study. The results of the analysis are waste management by reducing, moving, recycling and final disposal of waste, making wastewater treatment plants using environmentally friendly sanitation technology, and making disposal sites and processing waste produced by placing several points in IKN. The implementation of waste management in the development of the IKN is important to ensure that the development does not harm the environment and society. By implementing proper waste management in the development of IKN.